Dog-assisted interventions to support health and wellbeing: a national survey of current practice in England - Shoesmith, Emily; Hall, Sophie S.; Riga, Evgenia; Mills, Daniel S.; Gibsone, Selina; McMillan, Dean; Wu, Qi; Clarke, Chris; Ratschen, Elena (Frontiers in Public Health, 2025)
IntroductionIn England, dog-assisted interventions (DAIs) are increasingly used to support the health and wellbeing of individuals with mental and physical health conditions. Although research in this area is increasing, little is known about the national prevalence and characteristics of DAIs in practice. Advancing knowledge is important to inform development of research, policy and practice in the field.MethodsAn online survey of DAI providers in England was conducted to collect data on DAI service provision, including target populations, session content and structure, implementation challenges, and best practices in dog selection, training, and welfare monitoring.ResultsOf 72 invitations sent to DAI organizations and therapists, 31 participants completed the survey (response rate: 41.3%). DAIs were primarily used to support individuals with mental health and neurodevelopmental conditions (e.g., anxiety, depression, autism) across the National Health Service (80.6%), private healthcare (61.3%), and educational settings (41.9%). Respondents estimated delivering DAIs across 7,679 institutions. Interventions included structured therapeutic sessions (61.3%) and spontaneous activities (51.6%), mostly delivered individually (90.5%) rather than to groups. Over half reported delivering dog-assisted therapy, but 38.7% were unsure whether sessions had individualized goals. Session frequency and duration varied; most lasted 31–60 min (54.8%) and occurred weekly (45.2%). Key challenges included limited access to delivery spaces (35.5%), infection control concerns (32.3%), and difficulties “matching” dogs to service users (22.6%). Dog selection relied on temperament assessments (100%). While 54.8% of handlers received formal training, content varied. Some were trained in dog body language and risk assessment; others were not. Welfare monitoring primarily depended on handler observation (90.3%) and access to basic resources such as water.DiscussionDAIs are now implemented in thousands of health, care and educational settings across England, serving diverse clinical populations of all ages, especially those with mental health and neurodevelopmental conditions. Interventions range from structured, goal-oriented sessions (e.g., supporting mental, emotional, or physical health) to spontaneous interactions (e.g., community programmes, social events, recreational activities). Participant responses highlight substantial variation in DAI characteristics and delivery. These findings underscore the clear need for standardized good practice guidelines encompassing aspects related to outcome reporting, dog selection and welfare monitoring, and provider training.